Understanding substitution impacts of harvested wood and processing residues to mitigate climate change: A case of Chattogram, Bangladesh - Tarit Kumar Baul; Anashuwa Chowdhury Atri; Umma Salma; Ashraful Alam; Mohammed Jashimuddin (Cleaner and Responsible Consumption, 2024)
In Bangladesh, the role of harvested wood (e.g. wood products and associated processing residues) to mitigate climate change is less known and often ignored. This study aims to understand the substitution impacts of harvested wood products and associated processing residues in Chattogram city area, Bangladesh. Additionally, we also explored sellers' and users' perceptions towards the use of wood biomass and associated effects, with users’ level of satisfaction with using different categories of products of wood, bamboo, steel, and plastic. The study only considered sawn wood from sawmills to the wooden furniture and building materials, and associated residues, but excluded carbon in the forest ecosystem. A survey, using three different types of pre-tested questionnaires consisting of open and close-ended questions, was carried out in 36 sawmills, 62 timber merchants, and 55 furniture manufacturers or shops, with their owners or managers in Chattogram City Corporation area, Bangladesh. We used the general displacement factors of 0.5, 0.45, 1, and 1.3 tC tC−1 for processing residues, composite wood furniture, solid wood furniture, and building materials, respectively. The amount of wood products and associated residues and their avoided emissions due to substitution were presented in m3 industry−1 year−1 and Mg industry−1 year−1. Results revealed that the highest mean annual consumptions of timber (783.95 m3 industry−1 year−1) and processing residues (196.05 m3 industry−1 year−1) were in the sawmills and the lowest (60.56 and 0.66 m3 industry−1 year−1) in the furniture manufacturers. Altogether, the processing of round logs generated 36% residues of its mass from sawmilling to furniture manufacture. Sawn wood (of sawmills and timber merchants) consumed in the building houses produced the highest annual avoided emissions (1029.51 Mg CO2 industry−1 year−1). The development of efficient products with long lifespans, in addition to factors such as forest management, emissions, waste generation, and life cycle assessments of products likely play a significant role in determining the overall impact on displacement factors. The future study should focus on developing material flow analysis integrated with a life cycle assessment approach for various products for the construction and associated sectors, thus generating a country-specific displacement factor. The perception-based study documented that wood furniture and processing residues as bioenergy were perceived as a good substitute for non-wood furniture (e.g., steel, plastic) and fossil fuels (gas, oil) and thus lowering fossil emissions as wood products were perceived as user-and-environment-friendly and attractive. However, environmental awareness of both consumers and sellers about wood and bioenergy use and forest degradation is crucial for turning them into positive from neutral perceptions.